Development of a Hand Gesture Detection-Based Robot System with MediaPipe - Selamat Muslimin; Ekawati Prihatini; Tri Martin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research presents the development of an intelligent robot that can be summoned simply by waving a hand, without the need for physical buttons or voice commands. The system utilizes MediaPipe technology to detect and recognize hand gestures in real time through a camera. When a user waves their hand toward the camera, the system processes the motion and identifies it as a signal to call the robot. Image processing is handled by a Raspberry Pi, while movement control is managed by an Arduino, which regulates the direction and speed of the motors. The robot automatically moves toward the user and stops at a certain point to wait for further confirmation. Test results show that the robot can accurately detect gestures under various lighting conditions and distances. This approach enables more natural and efficient human–robot interaction, making it well-suited for modern contactless service systems